ENGAGEMENT OF N15 IN YEAST PROTEINS Candida guilliermondii WKM U-42 (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The question about protein biosynthesis in yeast cells under conditions of nitrogen starvation was investigated after reconditioning of normal nutrition. Valin-N15 exchange and engagement of N15 in summary protein and in several amino acids of yeasts Candida guilliermondii WKM U-42 has shown the unequal protein anabolism during the recondition of nitrogen nutrition of starved yeasts.